Analysis of Substrate, Gastric Content and Nutrient Content of Varuna litterata - Sorbakti Sinaga; Maheno Sri Widodo; Yunita Maimunah (Postgraduate, University of Mataram, 2024)
Varuna litterata is a secondary freshwater crab found in tidal areas. This crab is caught, its eggs are taken, and it is considered a delicacy. Continuous fishing without any cultivation efforts can cause a decline in the population, leading to extinction. This study aims to determine the characteristics of the habitat substrate, stomach, and nutritional content of V. litterata. The method used in this study is descriptive exploratory. The study was conducted in the Serayu River for four months (October 2023 - January 2024). The observation location was carried out at three stations. The study showed that V. litterata prefers waters with clay sand substrates (75% sand, 25% dust, and 0% clay). This habitat is very suitable for cultivation development, as shown by the population of captured crabs. The results of observations of stomach contents show that this crab is an opportunistic omnivore. This crab has a high nutritional content with an average water content (60.72%), ash (4.57%), fat (0.52%), protein (25.66%), and carbohydrates (8.52%). Further research is essential to understand the reproductive system of V. litterata, its life cycle, and suitable habitats for spawning.